'My experience of school': the perspective of adopted young people aged 16–21 years. (2nd January 2022) - Templeton, Fiona; McGlade, Anne; Fitzsimons, Lelia
ABSTRACT: In terms of data, young people who have been adopted are an invisible population in Northern Ireland schools. With increasing knowledge of the impact of being an adoptee and adverse childhood experiences, and greater understanding of the importance of attachment, more research into the school experience of adopted young people is necessary. This study aimed to capture the perspective of adoptees aged 16–21 years on the impact of being an adoptee and their experience of mainstream school in Northern Ireland. Data was collected through one-to-one, face-to-face interviews with nine participants. Interviews were recorded, transcribed and analysed thematically using NVivo. The findings were in keeping with the main themes identified in a review of international literature exploring the experience of adopted children in school. While every participant's experience was unique, common challenges in school, as a result of the impact of their early life experiences, could be identified. How teachers responded to the needs of the participants was a key determinant in their overall experience of school. The study revealed that not every member of staff or school provided the support and understanding that was needed and this had a detrimental impact on the participant's emotional well-being and their ability to thrive. However, when the staff and culture of the school was informed, empathetic and supportive, participants overcame challenges and experienced success.